Back Pain Beliefs Are Related to the Impact of Low Back Pain in Baby Boomers in the Busselton Healthy Aging Study - Beales, Darren; Smith, Anne; O'Sullivan, Peter; Hunter, M.; Straker, Leon (American Physical Therapy Association, 2015)
Background: Back pain beliefs (BPBs) are an important modifiable factor related to disability associated with low back pain (LBP). Back pain beliefs have not been characterized in baby boomers, a group at risk for decreased activity levels and reduced productivity. Objective: The aims of this study were: (1) to identify factors related to BPBs and (2) to evaluate the association between LBP disability and beliefs. Design: A cross-sectional survey of community-dwelling baby boomers (born 1946–1964) was conducted. Methods: Nine hundred fifty-eight baby boomers (mean age=56.2 years) participating in the Busselton Healthy Aging Study provided their history of LBP, BPBs, LBP behaviors related to care seeking (taking medication, seeking professional help) and activity modification (missing work, interference with normal activities, interference with recreational activities), LBP-related disability, and additional covariates with known associations with BPBs. Regression analyses were used to: (1) identify factors associated with more positive beliefs and (2) test the association between more positive BPBs and lower LBP disability, independent of other correlates of BPBs.Results: More positive BPBs were associated with younger age, better mental well-being, and higher income, whereas more negative BPBs were associated with receiving sickness or disability benefits and the experience of LBP in the previous month. In participants who reported experiencing LBP within the previous month, more positive BPBs were associated with lower disability scale scores and a decreased probability of interference with usual activities, independent of pain intensity, age, mental well-being, income, and employment status. Limitations: Cross-sectional analysis limits assessment of causality. Conclusions: Poorer BPBs were associated with greater disability. Characterization of the relationships between BPBs and LBP-associated behaviors and disability in baby boomers can assist in developing interventions to improve activity participation and productivity, potentially reducing the burden of LBP in this age group.